Cellular Physiology and Metabolism of Physical Exercise - Luzi, Livio; SpringerLink (Online service) (Milano : Springer Milan, 2012)
The book covers areas of cellular physiology and metabolism that are of interest to scientists involved in research in diabetes and metabolic diseases. Some chapters of the book are specifically research-oriented, as all the authors are actively practicing either bench or clinical research in the area. Nonetheless, since the work is fully comprehensive of the discipline, it is also suitable for university classes of graduate and undergraduate students. In particular, the book discusses classical aspects of cellular physiology and the metabolism of physical exercise, as well as novel topics like exercise in transplantation and exercise in beta-cell failure, which mark the frontiers of research in sport-related sciences and research. Exercise physiologists, biologists and physicians are the specific professional and academic targets of this work. The team of authors together with the editor are world-renowned experts in the field of physiology and metabolism applied to sport sciences.
Keywords: Medicine; Human physiology; Diabetes; Metabolism; Cytology; Biomedicine; Human Physiology; Molecular Medicine; Diabetes; Metabolomics; Cell Biology